Perchement et réalités fortifiées en Méditerranée et en Europe, véme-xéme siecles = Fortified hilltop settlements in the Mediterranean and in Europe (5th-10th centuries) - Pergola, Philippe,; Castiglia, Gabriele,; Hanna, Elie Essa Kas,; Martinetto, Ilaria,; Segura, Jean-Antoine, (Limina/limites. Archaeologies, histories, islands and borders in the Mediterranean (365-1556) ;, 2023)
The result of an international congress (Roquebrune-sur-Argens, October 2019) about the fortified hilltop settlements of Late Antiquity and the Early Middle Ages, papers present both brand new data and syntheses on wide contexts throughout the European continent, the Mediterranean basin and beyond.